The potential risk of spinal cord injury from pedicle screw at the apex of adolescent idiopathic thoracic scoliosis: magnetic resonance imaging evaluation. Issue 1 (December 2015) - Wang, Shoufeng; Qiu, Yong; Liu, Wenjun; Shi, Benlong; Wang, Bin; Yu, Yang; Zhu, Zezhang; Qian, Bangping; Zhu, Feng; Sun, Xu
Abstract Background The pedicle screw placement in scoliosis correction at the apex underlies potential risk for neurological injury. This research is to investigate the relative position of spinal cord at the apex in idiopathic thoracic scoliosis and to explore the risk of spinal cord injury from pedicle screw at the apex. Methods Thirty-three adolescents with thoracic scoliosis were recruited in this study. The relative position of the spinal cord in the spinal canal was calculated by measuring the distance between the spinal cord and the medial wall of the pedicle on the convex and concave side through the axial plane of the apex in T2 weighted MR image. The distance from the spinal cord to the medial wall of pedicle between concave and convex side was compared respectively. The percentage of patients was calculated according to hypothesized different space (0 mm, less than 1 mm and less than 2 mm) between medial wall of pedicle and spinal cord at the apex. Results The average distance from the spinal cord to the medial wall of pedicle at the concave side was significantly less than that at the convex side (p =  0.000) of the apex in the major thoracic curves before operation. In the concave side of the apex, the percentage of patients was 39.4, 66.7, 84. 5 % in hypothesized space (0 mm, less than 1 mm and less than 2 mm) between medial wall of pedicle and spinal cord. However, in the convex side of apex, the percentage of cases was 0, 0, 3.0 % in the same hypothesized space respectively. Conclusions The screw placement is at a higher risk of spinal cord injury on the concave side than that on the convex side of apex in thoracic curve in MRI images. The screw placement in the concave side of apex should be evaluated carefully with MRI before operation.